El equilibrio de seguridad liderado por Francia frente a la OTAN - Tekir, Gökhan (2023)
The much-discussed question of the relevance of NATO after the end of the Cold War is reappearing due to increasing disagreements between the United States of America (USA) and the European Union (EU). The search of strategic autonomy of European countries led by France leads to questioning of the trans-Atlantic alliance. This questioning has become visible especially after the election of U.S. President Donald Trump, who expressed his doubts about the relevance of NATO. While the USA is disengaging with security issues related with European security, European countries are searching ways to find a common security and defense policy. The French President Emmanuel Macron has laid out several initiatives such as Permanent Structure Cooperation (PESCO), which aims at coordinating and deepening defense cooperation among EU member countries and European Intervention Initiative (EI2), which shares the goals of PESCO but operates outside EU framework. Although these initiatives are referred officially as complementary structures to NATO, they reflect Europe’s desire to break free from U.S. security umbrella and become an independent political body in world politics. France, which has traditionally been wary of U.S. security dominance over Europe, is taking the lead in structuring European security institutions and merging France’s interest with European interests.